A study on Blockchain & Its Technology (Trinity Journal of Management, IT & Media (TJMITM), 2022)
A blockchain is essentially a distributed database of records or public ledger of all transaction or digital events that have been executed and shared among participating parties. Each transaction in the public ledger is verified by consensus of a majority of the participating in the system. And, once entered, information can never be erased. the blockchain contains a certain and verifiable record of every single transaction ever made Bitcoin, the decentralized peer to peer digital currency, is the most popular example that uses blockchain technology. the digital currency bitcoin itself is highly controversial but the underlying blockchain technology has worked flawlessly and found wide range of application in both financial and non -financial world. This concept is enabled by “Blockchain” technology is proposed as a research project in 1991, the blockchain concept predated its first widespread application in use: Bitcoin, in 2009. In the years since, the use of blockchain has exploded via the creation of various cryptocurrencies, decentralized fiancé (Defi) applications, non-fungible tokens (NFTs) , and smart contracts
Keywords: Blockchain; Bitcoin; Concerns; cryptocurrencies